Pengaruh Narasi dan Budaya Lokal dalam Film Ngeri-Ngeri Sedap terhadap Komunikasi Pariwisata melalui Ulasan Penonton - Hasan Hasan; Hengky Dar Praguseno; Muhammad Fattah Rinjani; Nabila Putri Hendriyani; Echa Ghaissani Putri Anugerah; Nariswari Nismara Nitisara; Arsih Amalia Chandra Permata; Wiyata Wiyata (Institut Nalanda, 2025)
This research aims to analyze the representation of Batak culture in the film Missing Home by Bene Dion Rajagukguk in relation to interpersonal communication and its impact on the development of tourism in North Sumatra, particularly Bukit Holbung. The method used is a qualitative approach with in-depth analysis of questionnaire data based on audience reviews. The findings indicate that the film successfully portrays the values of custom, interpersonal communication, and the dynamics of Batak families authentically, thereby increasing public interest in visiting the filming locations. Additionally, the increase in tourist visits to Bukit Holbung following the film's screening has a positive impact on the local economy through the development of facilities and products managed by local BUMDES (village-owned enterprises). The implications of this research emphasize the importance of film media as an effective means of promoting culture and tourism, while also encouraging the preservation of traditional values in a modern context. This research is expected to serve as a reference for the development of culture-based tourism and intercultural communication in Indonesia.